Good Governance dalam Pemerintahan Indonesia: Analisis Normatif Berdasarkan Fikih Siyasah - Wise Wilujeng (Universitas Pangeran Diponegoro Nganjuk, 2025)
This study examines the concept of Good Governance in Indonesian governance through the normative perspective of fiqh siyasah (Islamic political jurisprudence). Fiqh siyasah provides a distinctive framework by grounding governance principles in the Qur’an and Hadith, thus offering an ethical and religious dimension to the formulation of good governance. The main objective of this research is to analyze how the principles of fiqh siyasah can be integrated into the implementation of good governance in order to address issues of corruption, inefficiency, and the decline of public trust in governmental institutions. This research employs a normative juridical approach, relying on library research that includes the collection and analysis of primary, secondary, and tertiary legal sources. The findings show that the principles of fiqh siyasah, such as justice (‘adl), accountability (mas’uliyyah), consultation (shura), and public welfare (maslahah) are highly relevant to the modern framework of good governance. The study concludes that adopting these principles can strengthen democratic institutions, improve public service quality, and serve as a corrective mechanism to minimize corruption and abuse of power. This research contributes to the discourse on Islamic legal thought by demonstrating its applicability in addressing contemporary governance challenges.